INTEGRATION OF THE TOOLS WHICH INCREASE EFFICIENCY OF LEARNING INTO THE EDUCATIONAL PROCESS ON THE EXAMPLE OF THE CURRICULUM (Journal of Information Technologies in Education (ITE), 2010)
The article is devoted to the issues of improving the effectiveness of learning through integration into a single integrated information data space, which are present in various computer systems.
Keywords: education; education provision; curriculum; integration of systems